23. Regional Variation in Outpatient Antibiotic Prescribing in a Commercially-insured Population, United States, 2017. (31st December 2020) - Bizune, Destani J; Palms, Danielle; King, Laura M; Bartoces, Monina; Link-Gelles, Ruth; Hicks, Lauri; Fleming-Dutra, Katherine E
Abstract: Background: Studies have shown that the Southern United States has higher rates of outpatient antibiotic prescribing compared to other regions in the country, but reasons for this variation are unclear. We aimed to determine whether the regional variability in outpatient antibiotic prescribing for respiratory diagnoses can be explained by differences in patient age, care setting, comorbidities, and diagnosis in a commercially-insured population. Methods: We analyzed the 2017 IBM® MarketScan® Commercial Database of commercially-insured individuals aged < 65 years. We included visits with acute respiratory tract infection (ARTI) diagnoses from retail clinics, urgent care centers, emergency departments, and physician offices. ARTI diagnoses were categorized as: Tier 1, antibiotics are almost always indicated (pneumonia); Tier 2, antibiotics are sometimes indicated (sinusitis, acute otitis media, pharyngitis); and Tier 3, antibiotics are not indicated (asthma, allergy, bronchitis, bronchiolitis, influenza, nonsuppurative otitis media, viral upper respiratory infections, viral pneumonia). We calculated risk ratios and 95% confidence intervals (CI) stratified by US Census region and ARTI tier using log-binomial models controlling for patient age, comorbidities (Elixhauser and Complex Chronic Conditions for Children), and setting of care, with Tier 3 visits in the West, the strata with the lowest antibiotic prescription rate, as the reference for all strata. Results: A total of 100, 104, 860 visits were analyzed. In multivariable modeling, ARTI visits in the South and Midwest were highly associated with receiving an antibiotic for Tier 2 conditions vs. patients in other regions (Figure 1). Figure 1. Multivariable model comparing risk of receiving an antibiotic for an ARTI by region and diagnostic tier in urgent care, retail health, emergency department, and office visits, MarketScan® 2017, United States Conclusion: Regional variability in outpatient antibiotic prescribing for Tier 2 and 3 ARTIs remained even after controlling for patient age, comorbidities, and setting of care. It is likely that this variability is in part due to non-clinical factors such as regional differences in clinicians' prescribing habits and patient expectations. Targeted and enhanced public health stewardship interventions are needed to address cultural factors that affect antibiotic prescribing in outpatient settings. Disclosures: All Authors : No reported disclosures